1996
DOI: 10.1183/09031936.96.09020328
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependency of surfactant phospholipids and surfactant protein A in bronchoalveolar lavage fluid of children without bronchopulmonary disease

Abstract: Whilst alterations in surfactant components of bronchoalveolar lavage fluid (BALF) have been described in a variety of pulmonary diseases in adults, no information is available on the surfactant composition in children beyond the neonatal period. In order to obtain reference values for the paediatric age group, we have studied phospholipid profiles of BALF in children without pulmonary disease.The study population consisted of 38 children aged 3-15 yrs (mean±SD 8±4 yrs) undergoing elective surgery for nonpulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…In a previous study, we showed that the concentration of surfactant phospholipids in BAL fluid is higher in children than in adults. 9,10 Higher local concentrations may lead to more lipid being ingested by alveolar macrophages in children than adults, resulting in a higher intracellular lipid concentration. In addition, the metabolism of surfactant may differ between children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we showed that the concentration of surfactant phospholipids in BAL fluid is higher in children than in adults. 9,10 Higher local concentrations may lead to more lipid being ingested by alveolar macrophages in children than adults, resulting in a higher intracellular lipid concentration. In addition, the metabolism of surfactant may differ between children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration of BAL fibronectin and hyaluronic acid in BALF are not different in children and adults [34,80,81]. Surfactant phospholipid concentrations are higher in children 3±8 yrs of age than in older children, whereas protein concentrations are independent of the child's age [83].…”
Section: Noncellular Bal Componentsmentioning
confidence: 92%
“…The mechanism proposed involves attenuation of cytosolic component translocations of the respiratory burst oxidase to the plasma membrane (80). Ratjen et al (81) reported age-dependency of surfactant phospholipids and surfactant protein A (SP-A) in bronchoalveolar lavage fluid from children without bronchopulmonary disease. HPLC using both UV and light-scattering detection was the analytical tool of choice.…”
Section: General Surfactant Analysismentioning
confidence: 99%